Le Prix Médiatine fête ses 10 ans au Botanique. - Desir, Georges; Thiel, Denise; Van Tieghem, Jean-Pierre; Wonner, Solange (Sint-Lambrechts-Woluwe : Médiatine - Cultureel Centrum, 1992)
Baibay, Marianne ; Bauclair, Guy ; Becerra, Carlos ; Cardoen, Philippe ; Casse, Béatrice ; Chabeau, Alain ; Chable, Thomas ; Clerbois, Michel ; Coeck, Didier ; Coster, Jocelyne ; d'Herbais de Thun, Nicole ; d'Oultremont, Juan ; Dandoy, Eric ; Debliquy, Daniel ; Docte, Philippe Le ; van den Driessche, Jan ; Dubuc, Evelyne ; François, Jean-Michel ; Heddrich, Mélanie ; Henrotin, Marc ; Iezzi, Jacques ; Jacquemin, Thierry ; Kral, Viviane ; Leon Morales, Hugo René ; Leukers, Véronique ; Linotte, Georges ; Moffarts, Michel ; Mouffe, Michel ; Novis, Paul ; Ollivero, Roberto ; Pasture, Marc ; Pirotte, Nathalie ; Spetschinsky, Katia ; Verheirstraeten, Rosy ; Wery, Bern
biog., ind. tent., gr. tent., prijzen, ... per kunstenaar
Frans
Le Prix Médiatine fête ses 10 ans au Botanique, 1992
boek